Comparative experimental study of the mechanical and fracture properties of Portland limestone and Corsehill sandstone (Fracture and Structural Integrity, 2019)
An experimental investigation of the mechanical and fracture characteristics of Portland limestone and Corsehill sandstone is undertaken, aiming at enhancing understanding of the structural behaviour of these natural building stones commonly used in both new and restoration projects in Edinburgh, Scotland. A series of three-point bending and four-point bending tests on appropriately cut prismatic samples, in the presence of U-shape notches, were performed and results were interpreted following the concepts of crack mouth opening displacement and fracture energy. The critical crack opening displacement could be further investigated as a fracture criterion, independently of the method used for its determination. At a second stage, the effect of specimen shape and size on flexural strength, deflection at mid-span, crack mouth opening displacement and fracture energy was studied for Portland limestone. Despite the scattering of results, trends observed comprise (a) the negative correlation between the flexural strength of Portland limestone and the specimen span length and (b) the positive correlation between fracture energy and specimen size. Conclusions drawn are in good agreement with similar ones for other quasi-brittle materials and contribute to the assessment of the fracture behaviour of full size structural members that are often beyond the range of possible failure testing.
Keywords: Corsehill sandstone; Portland limestone; Mechanical properties; Size effect; Shape effect; Fracture energy